Seepage Analysis of the Earth Dam of a Reservoir Based on Measured Piezometer Data - LIU Fengru; BOLANHAN·Kaiken; ZHAN Damei (Renmin Zhujiang)
Dam seepage is one of the main factors endangering dam safety,especially for earth-rock dam.Taking the homogeneous earth dam of a reservoir as the example,this paper analyzes the measured piezometer data,and calculates and analyzes the seepage field of the typical dam section under typical stable and transient working conditions by the finite element method for obtaining the pore pressure distribution law,and comparing it with the measured value.The results show that:The distance between piezometer and upstream dam toe is negatively correlated with piezometer water level,and the change trend of piezometer water level is basically consistent with that of reservoir water level;The isopotential line is deflected at the material partition,and dense at the cutoff wall,and the phreatic line and release point below the cutoff wall lower;The measured and theoretical values of phreatic line coincide well,which increase or decrease with the reservoir water level with good correlation;The seepage gradient at the release point under each working condition is less than the allowable gradient,and the seepage stability of the dam meets the requirements.